Retrieval of surface-layer moisture fields using CSU radars - Fritz, Jason, author; Chandrasekar, Chandra V., author (Colorado State University. Libraries, 2006)
The surface-layer refractivity, i.e., the refractive index of air near the earth's surface, can be retrieved from radar by examining the phase of stationary ground targets. The index of refraction is a function of pressure, temperature, and humidity, and variations are dominated by humidity in warmer weather. Since the refractivity has a significant impact on the phase of propagating radar waves, it can be measured by observing the range integrated phase change between two stationary ground targets. This index, in turn, can be used to estimate the water vapor near the surface to explore convective storm initiation and storm evolution, and to enhance quantitative precipitation forecasts. This procedure was recently performed using the CSU-CHILL and Pawnee s-band radars, in addition to several other radars and sensors in Colorado. Estimated refractivity fields and the result of automatic stationary target identification are presented as well as phase comparisons with an x-band radar.
Keywords: phase processing; refractivity; radar